Domestic Violence Against Women and Mental Health - Taycan, O.; Uygun, E.; Karabulut, E. (Turkish Medical Association, 2020)
In addition to the difficulties caused bymigration, it also involves many potentials and opportunities. Otherwise it wouldn’t makemuch sense; why would people leave their homes, countries, a familiar life and throw themselves into the arms of the unknown? In this article, the phenomenon of migration, which is multilayered and complex in any case, is tried to be discussed from the perspective of community mental health. © 2020, Turkish Medical Association. All rights reserved.
GÖÇ VE TOPLUM RUH SAĞLIĞI: ARAFTA KALAN YAŞAMLAR
Keywords: Community Mental Health; İmmigrant; Migration; Refugee